Bhikhu Parekh's Thought on Multiculturalism: A Relevance to Indonesia's Management of Ethnic and Religious Conflicts - Sahfutra, Suryo Adi; Supartiningsih; Agus Himmawan Utomo (Andalas International Journal of Socio-Humanities, 2024)
Bhikhu Parekh's conceptualization of multiculturalism offers a significant contribution to the theoretical and practical debates surrounding multiculturalism in highly diverse urban societies. In the realm of theory, Parekh's notions of multiculturalism provide an alternative discourse to the prevailing emphasis on individual and minority rights within liberal frameworks. Conceptually, Parekh categorizes cultural diversity in modern/urban societies into three forms: 1) subcultural diversity; 2) perspectival diversity; 3) communal diversity. Furthermore, he divides multiculturalism into several models, including isolationist multiculturalism, accommodative multiculturalism, autonomous multiculturalism, interactive multiculturalism, and cosmopolitan multiculturalism. This philosophical perspective on multiculturalism holds relevance in the context of managing ethnic and religious diversity in Indonesia. It underscores the emergence of awareness and 'sensitivity' to differences, starting with political and religious leaders becoming more attuned to the diversity of distinctions.